Integrating biodiversity into land-use regulations: Evidence from Swiss municipal plan revisions - Stephanie Schwab Cammarano; Marco Moretti; Rolf Holderegger; Florian Altermatt; Anna M. Hersperger (Urban Forestry & Urban Greening, 2026)

Population genomics for biodiversity conservation: Insights from the Swiss pilot study for monitoring genetic diversity - Martin C. Fischer; Oliver Reutimann; Niklaus Zemp; Alessia Guggisberg; Felix Gugerli; Rolf Holderegger; Alex Widmer (Conservation Genetics, 2026)
Genetic diversity is the raw material of evolution and is essential for adaptation and survival. Concerted efforts have been made under the Kunming-Montreal Global Biodiversity Framework (GBF) to incorporate intraspecific genetic diversity into national monitoring efforts. Much emphasis has been put on non-genetic proxies of genetic diversity, due to the limited amount of genetic data currently available on species and their populations globally. Genomic data, however, provide a much more detailed perspective on intraspecific genetic diversity, revealing the demographic history, genetic structure and vulnerability of populations. To build capacity, knowledge and experience on the use of genomic data in biodiversity monitoring, we conducted a population genomic pilot study in Switzerland. We assessed five animal and plant species that are associated with habitats of national importance and anthropogenically modified landscapes. To achieve a representative, unbiased sampling of populations, we developed a proportional stratified random sampling strategy. We de novo assembled the reference genome of each species and re-sequenced 1,200 individuals. For two species, we also sequenced 400 historical samples to retrospectively assess temporal changes in genetic diversity. The genomic data allowed for detailed inference on the extent and spatial distribution of genetic diversity, connectivity and adaptive genetic variation. Changes in population inbreeding and effective population size ( N e ) were inferred back in time for 100 generations, providing insights that would otherwise require long-term monitoring. The results were summarised into five intuitive population genomic diversity variables and indicators for reporting to national authorities and stakeholders. We discuss the feasibility, strengths and potential limitations of our population genomic monitoring approach and conclude that a national monitoring of genetic diversity using whole-genome re-sequencing is nowadays technically and bioinformatically achievable, especially in the Global North. The knowledge gained has high potential to contribute to conservation actions that support the GBF key action of maintaining within-species genetic diversity to safeguard the adaptive potential of species.

Positive developments in low-intensive, protected grasslands in Switzerland suggest successful conservation measures - Steffen Boch; Klaus T. Ecker; Noémie A. Pichon; Angéline Bedolla; Rolf Holderegger; Tobias Moser; Ariel Bergamini (Biological Conservation, 2026)

Building pondscapes for amphibian metapopulations - Helen Moor; Ariel Bergamini; Christoph Vorburger; Rolf Holderegger; Christoph Bühler; Nicolas Bircher; Benedikt R. Schmidt (Conservation Biology, 2024)
The success of ponds constructed to restore ecological infrastructure for pond‐breeding amphibians and benefit aquatic biodiversity depends on where and how they are built. We studied effects of pond and landscape characteristics, including connectivity, on metapopulation dynamics of 12 amphibian species in Switzerland. To understand the determinants of long‐term occupancy (here summarized as incidence), environmental effects on both colonization and persistence should be considered. We fitted dynamic occupancy models to 20 years of monitoring data on a pond construction program to quantify effects of pond and landscape characteristics and different connectivity metrics on colonization and persistence probabilities in constructed ponds. Connectivity to existing populations explained dynamics better than structural connectivity metrics, and simple metrics (distance to the nearest neighbor population, population density) were useful surrogates for dispersal kernel‐weighted metrics commonly used in metapopulation theory. Population connectivity mediated the persistence of conservation target species in new ponds, suggesting source–sink dynamics in newly established populations. Population density captured this effect well and could be used by practitioners for site selection. Ponds created where there were 2–4 occupied ponds within a radius of ∼0.5 km had >3.5 times higher incidence of target species (median) than isolated ponds. Species had individual preferences regarding pond characteristics, but breeding sites with larger (≥100 m 2 ) total water surface area, that temporarily dried, and that were in surroundings with maximally 50% forest benefitted multiple target species. Pond diversity will foster amphibian diversity at the landscape scale.

Clonal genomic population structure of Beauveria brongniartii and Beauveria pseudobassiana : Pathogens of the common European cockchafer ( Melolontha melolontha L.) - Chiara Pedrazzini; Stephen A. Rehner; Hermann Strasser; Niklaus Zemp; Rolf Holderegger; Franco Widmer; Jürg Enkerli (Environmental Microbiology, 2024)
Beauveria brongniartii is a fungal pathogen that infects the beetle Melolontha melolontha , a significant agricultural pest in Europe. While research has primarily focused on the use of B. brongniartii for controlling M. melolontha , the genomic structure of the B. brongniartii population remains unknown. This includes whether its structure is influenced by its interaction with M. melolontha , the timing of beetle‐swarming flights, geographical factors, or reproductive mode. To address this, we analysed genome‐wide SNPs to infer the population genomics of Beauveria spp., which were isolated from infected M. melolontha adults in an Alpine region. Surprisingly, only one‐third of the isolates were identified as B. brongniartii , while two‐thirds were distributed among cryptic taxa within B. pseudobassiana , a fungal species not previously recognized as a pathogen of M. melolontha . Given the prevalence of B. pseudobassiana , we conducted analyses on both species. We found no spatial or temporal genomic patterns within either species and no correlation with the population structure of M. melolontha , suggesting that the dispersal of the fungi is independent of the beetle. Both species exhibited clonal population structures, with B. brongniartii fixed for one mating type and B. pseudobassiana displaying both mating types. This implies that factors other than mating compatibility limit sexual reproduction. We conclude that the population genomic structure of Beauveria spp. is primarily influenced by predominant asexual reproduction and dispersal.

Re-thinking the environment in landscape genomics - Benjamin Dauphin; Christian Rellstab; Rafael O. Wüest; Dirk N. Karger; Rolf Holderegger; Felix Gugerli; Stéphanie Manel (Trends in Ecology & Evolution, 2023)

Neither connectivity nor genetic diversity matter in the conservation of a rare fern and a moss on insular erratic boulders - Daniel Hepenstrick; Niklaus Zemp; Alex Widmer; Rolf Holderegger (Conservation Genetics, 2022)
Erratic boulders provide habitat for rock-dwelling species and contribute to the biodiversity of landscapes. In the calcareous Swiss lowlands, siliceous erratic boulders are exclusive habitat islands for the regionally critically endangered fern Asplenium septentrionale , about 20 bryophyte species and numerous lichens. Focusing on island biogeographical processes, we analysed the conservation genomics of A. septentrionale and the moss Hedwigia ciliata on insular erratic boulders in the Swiss lowlands and the adjacent “mainland” in siliceous mountains. We genotyped both species using double digest restriction associated DNA sequencing (ddRAD). For the tetraploid A. septentrionale , abundant identical multilocus genotypes within populations suggested prevalent intragametophytic selfing, and six out of eight boulder populations consisting of a single multilocus genotype each indicated single spore founder events. The genetic structure of A. septentrionale mainland populations coincided with Pleistocene glacial refugia. Four genetic lineages of H. ciliata were identified, and populations consisting of a single multilocus genotype were less common than in A. septentrionale . For both taxa, multilocus genotype diversity on boulders was lower than in mainland populations. The absence of common genetic groups among boulder populations, and the absence of isolation by distance patterns, suggested colonisation of boulders through independent long-distance dispersal events. Successful boulder colonisation of A. septentrionale seems to be rare, while colonisation by H. ciliata appears to be more frequent. We conclude that pivotal principles of conservation biology, such as connectivity and genetic diversity, are of less importance for the studied cryptogams on insular erratic boulders because of long-distance dispersal, intragametophytic selfing and polyploidy.

Developing a monitoring program of genetic diversity: what do stakeholders say? - Rea Pärli; Eva Lieberherr; Rolf Holderegger; Felix Gugerli; Alex Widmer; Martin C. Fischer (Conservation Genetics, 2021)
Genetic diversity is a fundamental component of biological diversity, and its conservation is considered key to ensure the long-term survival of natural populations and species. National and international legislation increasingly mandates a monitoring of genetic diversity. Examples are the United Nation’s Convention on Biological Diversity (CBD) Aichi target 13 and the current post-2020 negotiations to specify a new target for maintaining genetic diversity. To date, only a few pilot projects have been launched that systematically monitor genetic diversity over time in natural populations of a broad variety of wild species. The Swiss Federal Office for the Environment mandated a feasibility study in 2019 for implementing a national monitoring of genetic diversity in natural populations. To obtain information on whether stakeholders are interested in such a systematic monitoring, what they would expect from such a monitoring and where they see respective caveats, we conducted an online survey, which 138 (42% of those surveyed) Swiss stakeholders answered. We find that Swiss stakeholders are generally aware of the lacking evidence regarding the status of genetic diversity in wild populations and species. Accordingly, most stakeholders are interested in a monitoring of genetic diversity and see opportunities for the application of its results in their work. Nevertheless, stakeholders also expressed concerns regarding financial resources and that the results of a genetic diversity monitoring program would not benefit conservation practice. Our findings highlight the importance of stakeholder engagement and demonstrate the value of a detailed stakeholder analysis prior to developing and implementing a genetic diversity monitoring program. A powerful tool for examining the constellation and interactions of the different stakeholders are social network analyses (SNAs). Finally, it is particularly important to communicate transparently about the possibilities and limitations of a genetic diversity monitoring program as well as to closely involve stakeholders from the beginning to increase the acceptance of genetic diversity monitoring and facilitate its implementation.

Ready-to-use workflows for the implementation of genetic tools in conservation management - Rolf Holderegger; Benedikt R. Schmidt; Christoph Grünig; Robert Meier; Daniela Csencsics; Martin Gassner; Christian Rellstab; André Stapfer (Conservation Genetics Resources, 2020)
We present a conservation genetics tool kit, which offers two ready-to-use workflows for the routine application of genetic methods in conservation management. The workflows were optimized for work load and costs and are accompanied by an easy-to-read and richly illustrated manual with guidelines regarding sampling design, sampling of genetic material, necessary permits, laboratory methods, statistical analyses and documentation of results in a practice-oriented way. The manual also provides a detailed interpretation help for the implementation of the results in conservation management. One workflow deals with the identification of pond-breeding amphibians based on metabarcoding and environmental DNA (eDNA) from water samples. This workflow also discriminates the morphologically similar water frogs ( Pelophylax sp.) and other closely related species (e.g. Triturus cristatus and T. carnifex ). The second workflow studies connectivity among populations using microsatellite markers. Its statistical analyses encompass the detection of genetic groups and historical, recent and current dispersal and gene flow. Using the two workflows does not involve academic research institutes; they can be applied by environmental consultancies, laboratories from the private sector, governmental agencies or non-governmental organisations. These and additional conservation genetic workflows will hopefully foster the routine use of genetic methods in conservation management.

Genomic signatures of convergent adaptation to Alpine environments in three Brassicaceae species - Christian Rellstab; Stefan Zoller; Christian Sailer; Andrew Tedder; Felix Gugerli; Kentaro K. Shimizu; Rolf Holderegger; Alex Widmer; Martin C. Fischer (Molecular Ecology, 2020)
It has long been discussed to what extent related species develop similar genetic mechanisms to adapt to similar environments. Most studies documenting such convergence have either used different lineages within species or surveyed only a limited portion of the genome. Here, we investigated whether similar or different sets of orthologous genes were involved in genetic adaptation of natural populations of three related plant species to similar environmental gradients in the Alps. We used whole‐genome pooled population sequencing to study genome‐wide SNP variation in 18 natural populations of three Brassicaceae ( Arabis alpina, Arabidopsis halleri, and Cardamine resedifolia ) from the Swiss Alps. We first de novo assembled draft reference genomes for all three species. We then ran population and landscape genomic analyses with ~3 million SNPs per species to look for shared genomic signatures of selection and adaptation in response to similar environmental gradients acting on these species. Genes with a signature of convergent adaptation were found at significantly higher numbers than expected by chance. The most closely related species pair showed the highest relative over‐representation of shared adaptation signatures. Moreover, the identified genes of convergent adaptation were enriched for nonsynonymous mutations, suggesting functional relevance of these genes, even though many of the identified candidate genes have hitherto unknown or poorly described functions based on comparison with Arabidopsis thaliana . We conclude that adaptation to heterogeneous Alpine environments in related species is partly driven by convergent evolution, but that most of the genomic signatures of adaptation remain species‐specific.

Disentangling the effects of geographic peripherality and habitat suitability on neutral and adaptive genetic variation in Swiss stone pine - Benjamin Dauphin; Rafael O. Wüest; Sabine Brodbeck; Stefan Zoller; Martin C. Fischer; Rolf Holderegger; Felix Gugerli; Christian Rellstab (Molecular Ecology, 2020)
It is generally accepted that the spatial distribution of neutral genetic diversity within a species’ native range mostly depends on effective population size, demographic history, and geographic position. However, it is unclear how genetic diversity at adaptive loci correlates with geographic peripherality or with habitat suitability within the ecological niche. Using exome‐wide genomic data and distribution maps of the Alpine range, we first tested whether geographic peripherality correlates with four measures of population genetic diversity at > 17,000 SNP loci in 24 Alpine populations (480 individuals) of Swiss stone pine ( Pinus cembra ) from Switzerland. To distinguish between neutral and adaptive SNP sets, we used four approaches (two gene diversity estimates, F ST outlier test, and environmental association analysis) that search for signatures of selection. Second, we established ecological niche models for P. cembra in the study range and investigated how habitat suitability correlates with genetic diversity at neutral and adaptive loci. All estimates of neutral genetic diversity decreased with geographic peripherality, but were uncorrelated with habitat suitability. However, heterozygosity ( H e ) at adaptive loci based on Tajima's D declined significantly with increasingly suitable conditions. No other diversity estimates at adaptive loci were correlated with habitat suitability. Our findings suggest that populations at the edge of a species' geographic distribution harbour limited neutral genetic diversity due to demographic properties. Moreover, we argue that populations from suitable habitats went through strong selection processes, are thus well adapted to local conditions, and therefore exhibit reduced genetic diversity at adaptive loci compared to populations at niche margins.

Conservation genetics: Linking science with practice - Rolf Holderegger; Niko Balkenhol; Janine Bolliger; Jan O. Engler; Felix Gugerli; Axel Hochkirch; Carsten Nowak; Gernot Segelbacher; Alex Widmer; Frank E. Zachos (Molecular Ecology, 2019)
Conservation genetics is a well‐established scientific field. However, limited information transfer between science and practice continues to hamper successful implementation of scientific knowledge in conservation practice and management. To mitigate this challenge, we have established a conservation genetics community, which entails an international exchange‐and‐skills platform related to genetic methods and approaches in conservation management. First, it allows for scientific exchange between researchers during annual conferences. Second, personal contact between conservation professionals and scientists is fostered by organising workshops and by popularising knowledge on conservation genetics methods and approaches in professional journals in national languages. Third, basic information on conservation genetics has been made accessible by publishing an easy‐to‐read handbook on conservation genetics for practitioners. Fourth, joint projects enabled practitioners and scientists to work closely together from the start of a project in order to establish a tight link between applied questions and scientific background. Fifth, standardised workflows simplifying the implementation of genetic tools in conservation management have been developed. By establishing common language and trust between scientists and practitioners, all these measures help conservation genetics to play a more prominent role in future conservation planning and management.

The phylogeographic structure of Arabis alpina in the Alps shows consistent patterns across different types of molecular markers and geographic scales - Aude Rogivue; René Graf; Christian Parisod; Rolf Holderegger; Felix Gugerli (Alpine Botany, 2018)

Celebrating 125 years of Alpine Botany - Jürg Stöcklin; Rolf Holderegger (Alpine Botany, 2016)

A practical guide to environmental association analysis in landscape genomics - Christian Rellstab; Felix Gugerli; Andrew J. Eckert; Angela M. Hancock; Rolf Holderegger (Molecular Ecology, 2015)
Landscape genomics is an emerging research field that aims to identify the environmental factors that shape adaptive genetic variation and the gene variants that drive local adaptation. Its development has been facilitated by next‐generation sequencing, which allows for screening thousands to millions of single nucleotide polymorphisms in many individuals and populations at reasonable costs. In parallel, data sets describing environmental factors have greatly improved and increasingly become publicly accessible. Accordingly, numerous analytical methods for environmental association studies have been developed. Environmental association analysis identifies genetic variants associated with particular environmental factors and has the potential to uncover adaptive patterns that are not discovered by traditional tests for the detection of outlier loci based on population genetic differentiation. We review methods for conducting environmental association analysis including categorical tests, logistic regressions, matrix correlations, general linear models and mixed effects models. We discuss the advantages and disadvantages of different approaches, provide a list of dedicated software packages and their specific properties, and stress the importance of incorporating neutral genetic structure in the analysis. We also touch on additional important aspects such as sampling design, environmental data preparation, pooled and reduced‐representation sequencing, candidate‐gene approaches, linearity of allele–environment associations and the combination of environmental association analyses with traditional outlier detection tests. We conclude by summarizing expected future directions in the field, such as the extension of statistical approaches, environmental association analysis for ecological gene annotation, and the need for replication and post hoc validation studies.

How to make landscape genetics beneficial for conservation management? - Daniela Keller; Rolf Holderegger; Maarten J. van Strien; Janine Bolliger (Conservation Genetics, 2015)

Directed dispersal by rotational shepherding supports landscape genetic connectivity in a calcareous grassland plant - Yessica Rico; Rolf Holderegger; Hans Juergen Boehmer; Helene H. Wagner (Molecular Ecology, 2014)
Directed dispersal by animal vectors has been found to have large effects on the structure and dynamics of plant populations adapted to frugivory. Yet, empirical data are lacking on the potential of directed dispersal by rotational grazing of domestic animals to mediate gene flow across the landscape. Here, we investigated the potential effect of large‐flock shepherding on landscape‐scale genetic structure in the calcareous grassland plant D ianthus carthusianorum , whose seeds lack morphological adaptations to dispersal to animals or wind. We found a significant pattern of genetic structure differentiating population within grazed patches of three nonoverlapping shepherding systems and populations of ungrazed patches. Among ungrazed patches, we found a strong and significant effect of isolation by distance ( r = 0.56). In contrast, genetic distance between grazed patches within the same herding system was unrelated to geographical distance but significantly related to distance along shepherding routes ( r = 0.44). This latter effect of connectivity along shepherding routes suggests that gene flow is spatially restricted occurring mostly between adjacent populations. While this study used nuclear markers that integrate gene flow by pollen and seed, the significant difference in the genetic structure between ungrazed patches and patches connected by large‐flock shepherding indicates the potential of directed seed dispersal by sheep across the landscape.

Population genomic footprints of selection and associations with climate in natural populations of Arabidopsis halleri from the Alps - Martin C. Fischer; Christian Rellstab; Andrew Tedder; Stefan Zoller; Felix Gugerli; Kentaro K. Shimizu; Rolf Holderegger; Alex Widmer (Molecular Ecology, 2013)
Natural genetic variation is essential for the adaptation of organisms to their local environment and to changing environmental conditions. Here, we examine genomewide patterns of nucleotide variation in natural populations of the outcrossing herb Arabidopsis halleri and associations with climatic variation among populations in the Alps. Using a pooled population sequencing (Pool‐Seq) approach, we discovered more than two million SNP s in five natural populations and identified highly differentiated genomic regions and SNP s using F ST ‐based analyses. We tested only the most strongly differentiated SNP s for associations with a nonredundant set of environmental factors using partial Mantel tests to identify topo‐climatic factors that may underlie the observed footprints of selection. Possible functions of genes showing signatures of selection were identified by Gene Ontology analysis. We found 175 genes to be highly associated with one or more of the five tested topo‐climatic factors. Of these, 23.4% had unknown functions. Genetic variation in four candidate genes was strongly associated with site water balance and solar radiation, and functional annotations were congruent with these environmental factors. Our results provide a genomewide perspective on the distribution of adaptive genetic variation in natural plant populations from a highly diverse and heterogeneous alpine environment.

Spatial scale affects landscape genetic analysis of a wetland grasshopper - Daniela Keller; Rolf Holderegger; Maarten J. van Strien (Molecular Ecology, 2013)
Most landscape genetic studies assess the impact of landscape elements on species' dispersal and gene flow. Many of these studies perform their analysis on all possible population pairs in a study area and do not explicitly consider the effects of spatial scale and population network topology on their results. Here, we examined the effects of spatial scale and population network topology on the outcome of a landscape genetic analysis. Additionally, we tested whether the relevant spatial scale of landscape genetic analysis could be defined by population network topology or by isolation‐by‐distance ( IBD ) patterns. A data set of the wetland grasshopper S tethophyma grossum , collected in a fragmented agricultural landscape, was used to analyse population network topology, IBD patterns and dispersal habitats, using least‐cost transect analysis. Landscape genetic analyses neglecting spatial scale and population network topology resulted in models with low fits, with which a most likely dispersal habitat could not be identified. In contrast, analyses considering spatial scale and population network topology resulted in high model fits by restricting landscape genetic analysis to smaller scales (0–3 km) and neighbouring populations, as represented by a G abriel graph. These models also successfully identified a likely dispersal habitat of S . grossum . The above results suggest that spatial scale and potentially population network topology should be more explicitly considered in future landscape genetic analyses.

Identifying genetic signatures of selection in a non-model species, alpine gentian (Gentiana nivalis L.), using a landscape genetic approach - Helen Bothwell; Sarah Bisbing; Nina Overgaard Therkildsen; Lindsay Crawford; Nadir Alvarez; Rolf Holderegger; Stéphanie Manel (Conservation Genetics, 2013)

An outlier locus relevant in habitat-mediated selection in an alpine plant across independent regional replicates - Dominique Buehler; Bénédicte N. Poncet; Rolf Holderegger; Stéphanie Manel; Pierre Taberlet; Felix Gugerli (Evolutionary Ecology, 2013)

Where do you come from, where do you go? Directional migration rates in landscape genetics - Rolf Holderegger; Felix Gugerli (Molecular Ecology, 2012)
Identifying landscape elements that influence gene flow and migration in wild species is the current main topic of landscape genetics. Most landscape genetic studies infer gene flow and migration from genetic distances among populations or individuals and statistically relate these measurements to landscape composition and configuration. This approach assumes symmetrical gene flow between pairs of populations. Such an assumption, however, will often be violated, especially in source–sink systems. Source populations provide more emigrants than they receive immigrants, and sink populations get many immigrants, but release few emigrants. Source–sink dynamics cannot be explored using common landscape genetic approaches relying on genetic distances. In this issue of Molecular Ecology , Andreasen et al . ( ) apply an alternative approach allowing them to infer asymmetrical migration. They use a Bayesian assignment test among objectively defined populations of mountain lions ( Puma concolor ) in western USA to estimate recent and directional migration rates. The study shows that an area with a high amount of wildlife refuges and low hunting pressure harbours a source population for mountain lion dispersal, while areas with high hunting pressures form sink populations; a result helpful in making informed decisions in conservation management.

European phylogeography of the epiphytic lichen fungus L obaria pulmonaria and its green algal symbiont - Ivo Widmer; Francesco Dal Grande; Laurent Excoffier; Rolf Holderegger; Christine Keller; Vladimir S. Mikryukov; Christoph Scheidegger (Molecular Ecology, 2012)
In lichen symbiosis, fungal and algal partners form close associations, often codispersed by vegetative propagules. Due to the particular interdependence, processes such as colonization, dispersal or genetic drift are expected to result in congruent patterns of genetic structure in the symbionts. To study the population structure of an obligate symbiotic system in E urope, we genotyped the fungal and algal symbionts of the epiphytic lichen L obaria pulmonaria at eight and seven microsatellite loci, respectively, and analysed about 4300 L . pulmonaria thalli from 142 populations from the species' E uropean distribution range. Based on a centroid approach, which localizes centres of genetic differentiation with a high frequency of geographically restricted alleles, we identified the South I taly– B alkan region as the primary glacial refugial area of the lichen symbiosis. Procrustean rotation analysis and a distance congruence test between the fungal and algal population graphs indicated general concordance between the phylogeographies of the symbionts. The incongruent patterns found in areas of postglacial recolonization may show the presence of an additional refugial area for the fungal symbiont, and the impact that horizontal photobiont transmission and different mutation rates of the symbionts have on their genotypic associations at a continental scale.

Genetic diversity in widespread species is not congruent with species richness in alpine plant communities - Pierre Taberlet; Niklaus E. Zimmermann; Thorsten Englisch; Andreas Tribsch; Rolf Holderegger; Nadir Alvarez; Harald Niklfeld; Gheorghe Coldea; Zbigniew Mirek; Atte Moilanen; Wolfgang Ahlmer; Paolo Ajmone Marsan; et al. (Ecology Letters, 2012)
The Convention on Biological Diversity ( CBD ) aims at the conservation of all three levels of biodiversity, that is, ecosystems, species and genes. Genetic diversity represents evolutionary potential and is important for ecosystem functioning. Unfortunately, genetic diversity in natural populations is hardly considered in conservation strategies because it is difficult to measure and has been hypothesised to co‐vary with species richness. This means that species richness is taken as a surrogate of genetic diversity in conservation planning, though their relationship has not been properly evaluated. We tested whether the genetic and species levels of biodiversity co‐vary, using a large‐scale and multi‐species approach. We chose the high‐mountain flora of the Alps and the Carpathians as study systems and demonstrate that species richness and genetic diversity are not correlated. Species richness thus cannot act as a surrogate for genetic diversity. Our results have important consequences for implementing the CBD when designing conservation strategies.

Genetic differentiation of the endemic grass species Deschampsia littoralis at pre-Alpine lakes - Markus Peintinger; Nils Arrigo; Sabine Brodbeck; Andreas Koller; Martina Imsand; Rolf Holderegger (Alpine Botany, 2012)

Tales of the unexpected: Phylogeography of the arctic‐alpine model plant Saxifraga oppositifolia (Saxifragaceae) revisited - MANUELA WINKLER; ANDREAS TRIBSCH; GERALD M. SCHNEEWEISS; SABINE BRODBECK; FELIX GUGERLI; ROLF HOLDEREGGER; RICHARD J. ABBOTT; PETER SCHÖNSWETTER (Molecular Ecology, 2012)
Arctic‐alpine biota occupy enormous areas in the Arctic and the northern hemisphere mountain ranges and have undergone major range shifts during their comparatively short history. The origins of individual arctic‐alpine species remain largely unknown. In the case of the Purple saxifrage, Saxifraga oppositifolia , an important model for arctic‐alpine plants, phylogeographic studies have remained inconclusive about early stages of the species’ spatiotemporal diversification but have provided evidence for long‐range colonization out of a presumed Beringian origin to cover today’s circumpolar range. We re‐evaluated the species’ large‐scale range dynamics based on a geographically extended sampling including crucial areas such as Central Asia and the (south‐)eastern European mountain ranges and employing up‐to‐date phylogeographic analyses of a plastid sequence data set and a more restricted AFLP data set. In accordance with previous studies, we detected two major plastid DNA lineages also reflected in AFLP divergence, suggesting a long and independent vicariant history. Although we were unable to determine the species’ area of origin, our results point to Europe (probably the Alps) and Central Asia, respectively, as the likely ancestral areas of the two main lineages. AFLP data suggested that contact areas between the two clades in the Carpathians, Northern Siberia and western Greenland were secondary. In marked contrast to high levels of diversity revealed in previous studies, populations from the major arctic refugium Beringia did not exhibit any plastid sequence polymorphism. Our study shows that adequate sampling of the southern, refugial populations is crucial for understanding the range dynamics of arctic‐alpine species.

A new analytical approach to landscape genetic modelling: least‐cost transect analysis and linear mixed models - MAARTEN J. VAN STRIEN; DANIELA KELLER; ROLF HOLDEREGGER (Molecular Ecology, 2012)
Landscape genetics aims to assess the effect of the landscape on intraspecific genetic structure. To quantify interdeme landscape structure, landscape genetics primarily uses landscape resistance surfaces (RSs) and least‐cost paths or straight‐line transects. However, both approaches have drawbacks. Parameterization of RSs is a subjective process, and least‐cost paths represent a single migration route. A transect‐based approach might oversimplify migration patterns by assuming rectilinear migration. To overcome these limitations, we combined these two methods in a new landscape genetic approach: least‐cost transect analysis (LCTA). Habitat‐matrix RSs were used to create least‐cost paths, which were subsequently buffered to form transects in which the abundance of several landscape elements was quantified. To maintain objectivity, this analysis was repeated so that each landscape element was in turn regarded as migration habitat. The relationship between explanatory variables and genetic distances was then assessed following a mixed modelling approach to account for the nonindependence of values in distance matrices. Subsequently, the best fitting model was selected using the statistic. We applied LCTA and the mixed modelling approach to an empirical genetic dataset on the endangered damselfly, Coenagrion mercuriale . We compared the results to those obtained from traditional least‐cost, effective and resistance distance analysis. We showed that LCTA is an objective approach that identifies both the most probable migration habitat and landscape elements that either inhibit or facilitate gene flow. Although we believe the statistical approach to be an improvement for the analysis of distance matrices in landscape genetics, more stringent testing is needed.

Broad‐scale adaptive genetic variation in alpine plants is driven by temperature and precipitation - STÉPHANIE MANEL; FELIX GUGERLI; WILFRIED THUILLER; NADIR ALVAREZ; PIERRE LEGENDRE; ROLF HOLDEREGGER; LUDOVIC GIELLY; PIERRE TABERLET (Molecular Ecology, 2012)
Identifying adaptive genetic variation is a challenging task, in particular in non‐model species for which genomic information is still limited or absent. Here, we studied distribution patterns of amplified fragment length polymorphisms (AFLPs) in response to environmental variation, in 13 alpine plant species consistently sampled across the entire European Alps. Multiple linear regressions were performed between AFLP allele frequencies per site as dependent variables and two categories of independent variables, namely Moran’s eigenvector map MEM variables (to account for spatial and unaccounted environmental variation, and historical demographic processes) and environmental variables. These associations allowed the identification of 153 loci of ecological relevance. Univariate regressions between allele frequency and each environmental factor further showed that loci of ecological relevance were mainly correlated with MEM variables. We found that precipitation and temperature were the best environmental predictors, whereas topographic factors were rarely involved in environmental associations. Climatic factors, subject to rapid variation as a result of the current global warming, are known to strongly influence the fate of alpine plants. Our study shows, for the first time for a large number of species, that the same environmental variables are drivers of plant adaptation at the scale of a whole biome, here the European Alps.

Adaptive landscape genetics: pitfalls and benefits - CHRISTIAN PARISOD; ROLF HOLDEREGGER (Molecular Ecology, 2012)
Landscape genetics offers a promising framework for assessing the interactions between the environment and adaptive genetic variation in natural populations. A recent workshop held at the University of Neuchatel brought together leading experts in this field to address current insights and future research directions in adaptive landscape genetics. Considerable amounts of genetic and/or environmental data can now be collected, but the forthcoming challenge is to do more with such manna. This requires a markedly better understanding of the genetic variation that is adaptive and prompts for advances in information management together with the development of a balance between theory and data. Moreover, showing the links between landscapes and adaptive genetic variation will ultimately move the field beyond association studies.

Development of microsatellite markers for the wetland grasshopper Stethophyma grossum - Daniela Keller; Esther Jung; Rolf Holderegger (Conservation Genetics Resources, 2012)

Forecasting changes in population genetic structure of alpine plants in response to global warming - FLORA JAY; STÉPHANIE MANEL; NADIR ALVAREZ; ERIC Y. DURAND; WILFRIED THUILLER; ROLF HOLDEREGGER; PIERRE TABERLET; OLIVIER FRANÇOIS (Molecular Ecology, 2012)
Species range shifts in response to climate and land use change are commonly forecasted with species distribution models based on species occurrence or abundance data. Although appealing, these models ignore the genetic structure of species, and the fact that different populations might respond in different ways because of adaptation to their environment. Here, we introduced ancestry distribution models, that is , statistical models of the spatial distribution of ancestry proportions, for forecasting intra‐specific changes based on genetic admixture instead of species occurrence data. Using multi‐locus genotypes and extensive geographic coverage of distribution data across the European Alps, we applied this approach to 20 alpine plant species considering a global increase in temperature from 0.25 to 4 °C. We forecasted the magnitudes of displacement of contact zones between plant populations potentially adapted to warmer environments and other populations. While a global trend of movement in a north‐east direction was predicted, the magnitude of displacement was species‐specific. For a temperature increase of 2 °C, contact zones were predicted to move by 92 km on average (minimum of 5 km, maximum of 212 km) and by 188 km for an increase of 4 °C (minimum of 11 km, maximum of 393 km). Intra‐specific turnover—measuring the extent of change in global population genetic structure—was generally found to be moderate for 2 °C of temperature warming. For 4 °C of warming, however, the models indicated substantial intra‐specific turnover for ten species. These results illustrate that, in spite of unavoidable simplifications, ancestry distribution models open new perspectives to forecast population genetic changes within species and complement more traditional distribution‐based approaches.

Effects of floral neighborhood on seed set and degree of outbreeding in a high-alpine cushion plant - Lea R. Wirth; Nickolas M. Waser; René Graf; Felix Gugerli; Urs Landergott; Andreas Erhardt; Hans Peter Linder; Rolf Holderegger (Oecologia, 2011)

Marie Brockmann-Jerosch and her influence on Alpine phylogeography - Rolf Holderegger; Conny Thiel-Egenter; Christian Parisod (Alpine Botany, 2011)

Considering spatial and temporal scale in landscape‐genetic studies of gene flow - COREY DEVIN ANDERSON; BRYAN K. EPPERSON; MARIE‐JOSÉE FORTIN; ROLF HOLDEREGGER; PATRICK M. A. JAMES; MICHAEL S. ROSENBERG; KIM T. SCRIBNER; STEPHEN SPEAR (Molecular Ecology, 2010)
Landscape features exist at multiple spatial and temporal scales, and these naturally affect spatial genetic structure and our ability to make inferences about gene flow. This article discusses how decisions about sampling of genotypes (including choices about analytical methods and genetic markers) should be driven by the scale of spatial genetic structure, the time frame that landscape features have existed in their current state, and all aspects of a species’ life history. Researchers should use caution when making inferences about gene flow, especially when the spatial extent of the study area is limited. The scale of sampling of the landscape introduces different features that may affect gene flow. Sampling grain should be smaller than the average home‐range size or dispersal distance of the study organism and, for raster data, existing research suggests that simplifying the thematic resolution into discrete classes may result in low power to detect effects on gene flow. Therefore, the methods used to characterize the landscape between sampling sites may be a primary determinant for the spatial scale at which analytical results are applicable, and the use of only one sampling scale for a particular statistical method may lead researchers to overlook important factors affecting gene flow. The particular analytical technique used to correlate landscape data and genetic data may also influence results; common landscape‐genetic methods may not be suitable for all study systems, particularly when the rate of landscape change is faster than can be resolved by common molecular markers.

Landscape genetics: where are we now? - ANDREW STORFER; MELANIE A. MURPHY; STEPHEN F. SPEAR; ROLF HOLDEREGGER; LISETTE P. WAITS (Molecular Ecology, 2010)
Landscape genetics has seen rapid growth in number of publications since the term was coined in 2003. An extensive literature search from 1998 to 2008 using keywords associated with landscape genetics yielded 655 articles encompassing a vast array of study organisms, study designs and methodology. These publications were screened to identify 174 studies that explicitly incorporated at least one landscape variable with genetic data. We systematically reviewed this set of papers to assess taxonomic and temporal trends in: (i) geographic regions studied; (ii) types of questions addressed; (iii) molecular markers used; (iv) statistical analyses used; and (v) types and nature of spatial data used. Overall, studies have occurred in geographic regions proximal to developed countries and more commonly in terrestrial vs. aquatic habitats. Questions most often focused on effects of barriers and/or landscape variables on gene flow. The most commonly used molecular markers were microsatellites and amplified fragment length polymorphism (AFLPs), with AFLPs used more frequently in plants than animals. Analysis methods were dominated by Mantel and assignment tests. We also assessed differences among journals to evaluate the uniformity of reporting and publication standards. Few studies presented an explicit study design or explicit descriptions of spatial extent. While some landscape variables such as topographic relief affected most species studied, effects were not universal, and some species appeared unaffected by the landscape. Effects of habitat fragmentation were mixed, with some species altering movement paths and others unaffected. Taken together, although some generalities emerged regarding effects of specific landscape variables, results varied, thereby reinforcing the need for species‐specific work. We conclude by: highlighting gaps in knowledge and methodology, providing guidelines to authors and reviewers of landscape genetics studies, and suggesting promising future directions of inquiry.

Perspectives on the use of landscape genetics to detect genetic adaptive variation in the field - STÉPHANIE MANEL; STÉPHANE JOOST; BRYAN K. EPPERSON; ROLF HOLDEREGGER; ANDREW STORFER; MICHAEL S. ROSENBERG; KIM T. SCRIBNER; AURÉLIE BONIN; MARIE‐JOSÉE FORTIN (Molecular Ecology, 2010)
Understanding the genetic basis of species adaptation in the context of global change poses one of the greatest challenges of this century. Although we have begun to understand the molecular basis of adaptation in those species for which whole genome sequences are available, the molecular basis of adaptation is still poorly understood for most non‐model species. In this paper, we outline major challenges and future research directions for correlating environmental factors with molecular markers to identify adaptive genetic variation, and point to research gaps in the application of landscape genetics to real‐world problems arising from global change, such as the ability of organisms to adapt over rapid time scales. High throughput sequencing generates vast quantities of molecular data to address the challenge of studying adaptive genetic variation in non‐model species. Here, we suggest that improvements in the sampling design should consider spatial dependence among sampled individuals. Then, we describe available statistical approaches for integrating spatial dependence into landscape analyses of adaptive genetic variation.

Tracking genes of ecological relevance using a genome scan in two independent regional population samples of Arabis alpina - BÉNÉDICTE N. PONCET; DORIS HERRMANN; FELIX GUGERLI; PIERRE TABERLET; ROLF HOLDEREGGER; LUDOVIC GIELLY; DELPHINE RIOUX; WILFRIED THUILLER; SERGE AUBERT; STÉPHANIE MANEL (Molecular Ecology, 2010)

Between-year variation in seed weights across altitudes in the high-alpine plant Eritrichium nanum - Lea R. Wirth; René Graf; Felix Gugerli; Urs Landergott; Rolf Holderegger (Plant Ecology, 2010)

Applications of landscape genetics in conservation biology: concepts and challenges - Gernot Segelbacher; Samuel A. Cushman; Bryan K. Epperson; Marie-Josée Fortin; Olivier Francois; Olivier J. Hardy; Rolf Holderegger; Pierre Taberlet; Lisette P. Waits; Stéphanie Manel (Conservation Genetics, 2010)

Characterization of microsatellite loci in Leucorrhinia caudalis, a rare dragonfly endangered throughout Europe - Daniela Keller; Sabine Brodbeck; Rolf Holderegger (Conservation Genetics Resources, 2009)

Concordant genetic breaks, identified by combining clustering and tessellation methods, in two co‐distributed alpine plant species - CONNY THIEL‐EGENTER; ROLF HOLDEREGGER; SABINE BRODBECK; FELIX GUGERLI (Molecular Ecology, 2009)
Natural genetic breaks may indicate limitations to gene flow or the presence of contact zones of previously isolated populations. Molecular evidence suggests that genetic breaks have aggregated in distinct geographical areas. We propose a new application of well‐established statistical methods for analysing multilocus genetic data to identify intraspecific genetic breaks. The methodological approach combines Bayesian clustering with a spatially explicit maximum‐difference algorithm to visualize and quantify breaks between clusters. We used amplified fragment length polymorphism data of two co‐distributed, silicicolous alpine plant species, Geum montanum and Geum reptans , exhaustively sampled on a consistent, regular grid over their entire range of the European Alps and the Carpathians. We found a distinct and highly similar allocation of genetic breaks in both species. The pattern of breaks did not conform to scenarios of glacial refugial survival, alternatively in peripheral refugia or on nunataks, as expected because of the species’ ecologies (late‐successional low alpine vs. early‐successional high alpine). Our findings rather substantiated the postulate of a general pattern of genetic breaks in alpine plants and corresponded well with biogeographical regions formerly described. Our approach could serve as a tool not only for landscape genetics and comparative phylogeography, but also for floristics or faunistics to compare biogeographic with phylogeographic breaks.

History or ecology? Substrate type as a major driver of patial genetic structure in Alpine plants - Nadir Alvarez; Conny Thiel‐Egenter; Andreas Tribsch; Rolf Holderegger; Stéphanie Manel; Peter Schönswetter; Pierre Taberlet; Sabine Brodbeck; Myriam Gaudeul; Ludovic Gielly; Philippe Küpfer; Guilhem Mansion; et al. (Ecology Letters, 2009)
Climatic history and ecology are considered the most important factors moulding the spatial pattern of genetic diversity. With the advent of molecular markers, species’ historical fates have been widely explored. However, it has remained speculative what role ecological factors have played in shaping spatial genetic structures within species. With an unprecedented, dense large‐scale sampling and genome‐screening, we tested how ecological factors have influenced the spatial genetic structures in Alpine plants. Here, we show that species growing on similar substrate types, largely determined by the nature of bedrock, displayed highly congruent spatial genetic structures. As the heterogeneous and disjunctive distribution of bedrock types in the Alps, decisive for refugial survival during the ice ages, is temporally stable, concerted post‐glacial migration routes emerged. Our multispecies study demonstrates the relevance of particular ecological factors in shaping genetic patterns, which should be considered when modelling species projective distributions under climate change scenarios.

A discussion of different types of glacial refugia used in mountain biogeography and phylogeography - Rolf Holderegger; Conny Thiel‐Egenter (Journal of Biogeography, 2009)
With the recent rise of phylogeography, the biogeography of mountain species (species with their current main distribution above timber line), especially their glacial history, has attracted renewed interest. In particular, the question of where mountain species survived the ice ages has been approached in many phylogeographical studies. The terminology of glacial refugia of mountain species is often confusing, contradictory or counter‐intuitive. Our aim is to clarify and simplify this terminology. First, we offer a general definition of the term glacial refugium for mountain species. Then, we discuss three main types of glacial refugia of mountain species, i.e. nunatak, peripheral and lowland refugia. We believe that the discrimination of these three types of glacial refugia is sufficient to describe the glacial survival of (most) mountain species. Finally, we argue that the terms in situ survival and ex situ survival and the term periglacial refugium should only be used to describe specific cases of glacial history. No simple classification system can adequately describe every kind of glacial refugium, but we propose that authors should focus on providing comprehensive descriptions of particular refugial situations instead of introducing new terminology.

Effects of species traits on the genetic diversity of high‐mountain plants: a multi‐species study across the Alps and the Carpathians - Conny Thiel‐Egenter; Felix Gugerli; Nadir Alvarez; Sabine Brodbeck; Elżbieta Cieślak; Licia Colli; Thorsten Englisch; Myriam Gaudeul; Ludovic Gielly; Grażyna Korbecka; Riccardo Negrini; Ovidiu Paun; et al. (Global Ecology and Biogeography, 2009)
Aim To test the influence of various species traits, elevation and phylogeographical history on the genetic diversity of high‐mountain plants in the Alps and Carpathians. Location The regular sampling grid comprised the whole range of the European Alps and the Carpathians. Methods Twenty‐two high‐mountain plant species were exhaustively sampled and their genetic diversity was assessed with amplified fragment length polymorphisms (AFLPs). ANOVAs were used to check for relationships between species traits and species genetic diversity, and to test whether genetic diversity was influenced by altitude and phylogeographical history (i.e. Alps versus Carpathians). Results In both mountain systems, species dispersed and pollinated by wind showed higher genetic diversity than species with self or insect pollination, and with animal‐ or gravity‐dispersed seeds. Only in the Alps did altitudinal range size affect species genetic diversity significantly: species with narrow altitudinal ranges in the highest vegetation belts had significantly higher genetic diversity than those expanding over wide altitudinal ranges. Genetic diversity was species specific and significantly higher in the Alps than in the Carpathians, but it was not influenced by elevation. Main conclusions Wind pollination and wind dispersal seem to foster high genetic diversity. However, species traits are often associated and their effects on genetic diversity cannot be clearly disentangled. As genetic diversity is species specific, comparisons across species need to be interpreted with care. Genetic diversity was generally lower in the Carpathians than in the Alps, due to higher topographical isolation of alpine habitats in the Carpathians and this mountain massif's divergent phylogeographical history. Elevation did not influence genetic diversity, challenging the long‐held view of decreasing genetic diversity with increasing elevation in mountain plants.

Insertions–Deletions in a Microsatellite Flanking Region May Be Resolved by Variation in Stuttering Patterns - Felix Gugerli; Sabine Brodbeck; Rolf Holderegger (Plant Molecular Biology Reporter, 2008)

Landscape‐level gene flow in Lobaria pulmonaria , an epiphytic lichen - SILKE WERTH; FELIX GUGERLI; ROLF HOLDEREGGER; HELENE H. WAGNER; DANIELA CSENCSICS; CHRISTOPH SCHEIDEGGER (Molecular Ecology, 2007)
Epiphytes are strongly affected by the population dynamics of their host trees. Owing to the spatio‐temporal dynamics of host tree populations, substantial dispersal rates — corresponding to high levels of gene flow — are needed for populations to persist in a landscape. However, several epiphytic lichens have been suggested to be dispersal‐limited, which leads to the expectation of low gene flow at the landscape scale. Here, we study landscape‐level genetic structure and gene flow of a putatively dispersal‐limited epiphytic lichen, Lobaria pulmonaria . The genetic structure of L. pulmonaria was quantified at three hierarchical levels, based on 923 thalli collected from 41 plots situated within a pasture–woodland landscape and genotyped at six fungal microsatellite loci. We found significant isolation by distance, and significant genetic differentiation both among sampling plots and among trees. Landscape configuration, i.e. the effect of a large open area separating two forested regions, did not leave a traceable pattern in genetic structure, as assessed with partial Mantel tests and analysis of molecular variance. Gene pools were spatially intermingled in the pasture–woodland landscape, as determined by Bayesian analysis of population structure. Evidence for local gene flow was found in a disturbed area that was mainly colonized from nearby sources. Our analyses indicated high rates of gene flow of L. pulmonaria among forest patches, which may reflect the historical connectedness of the landscape through gene movement. These results support the conclusion that dispersal in L. pulmonaria is rather effective, but not spatially unrestricted.

Allelic configuration and polysomic inheritance of highly variable microsatellites in tetraploid gynodioecious Thymus praecox agg. - Urs Landergott; Yamama Naciri; J. Jakob Schneller; Rolf Holderegger (Theoretical and Applied Genetics, 2006)

Effect of disturbances on the genetic diversity of an old‐forest associated lichen - SILKE WERTH; HELENE H. WAGNER; ROLF HOLDEREGGER; JESSE M. KALWIJ; CHRISTOPH SCHEIDEGGER (Molecular Ecology, 2006)
Lichens associated with old forest are commonly assumed to be negatively affected by tree logging or natural disturbances. However, in this study performed in a spruce‐dominated sylvopastoral landscape in the Swiss Jura Mountains, we found that genetic diversity of the epiphytic old‐forest lichen Lobaria pulmonaria depends on the type of disturbance. We collected 923 thalli from 41 sampling plots of 1 ha corresponding to the categories stand‐replacing disturbance ( burnt ), intensive logging ( logged ) and uneven‐aged forestry ( uneven‐aged ), and analysed the thalli at six mycobiont‐specific microsatellite loci. We found evidence for multiple independent immigrations into demes located in burnt and logged areas. Using spatial autocorrelation methods, the spatial scale of the genetic structure caused by the clonal and recombinant component of genetic variation was determined. Spatial autocorrelation of genotype diversity was strong at short distances up to 50 m in logged demes, up to 100 m in uneven‐aged demes, with the strongest autocorrelation up to 150 m for burnt demes. The spatial autocorrelation was predominantly attributed to clonal dispersal of vegetative propagules. After accounting for the clonal component, we did not find significant spatial autocorrelation in gene diversity. This pattern may indicate low dispersal ranges of clonal propagules, but random dispersal of sexual ascospores. Genetic diversity was highest in logged demes, and lowest in burnt demes. Our results suggest that genetic diversity of epiphytic lichen demes may not necessarily be impacted by stand‐level disturbances for extended time periods.

Book review - Rolf Holderegger (Plant Systematics and Evolution, 2005)

Microsatellites reveal regional population differentiation and isolation in Lobaria pulmonaria , an epiphytic lichen - JEAN‐CLAUDE WALSER; ROLF HOLDEREGGER; FELIX GUGERLI; SUSAN EVA HOEBEE; CHRISTOPH SCHEIDEGGER (Molecular Ecology, 2005)
Many lichen species produce both sexual and asexual propagules, but, aside from being minute, these diaspores lack special adaptations for long‐distance dispersal. So far, molecular studies have not directly addressed isolation and genetic differentiation of lichen populations, both being affected by gene flow, at a regional scale. We used six mycobiont‐specific microsatellite loci to investigate the population genetic structure of the epiphytic lichen Lobaria pulmonaria in two regions that strongly differed with respect to anthropogenic impact. In British Columbia, L. pulmonaria grows in continuous old‐growth forests, while its populations in the old cultural landscape of Switzerland are comparably small and fragmented. Populations from both British Columbia and Switzerland were genetically diverse at the loci. Geographically restricted alleles, low historical gene flow, and analyses of genetic distance ( upgma tree) and of differentiation ( amova ) indicated that populations from Vancouver Island and from the Canadian mainland were separated from each other, except for one, geographically intermediate population. This differentiation was attributed to different glacial and postglacial histories of coastal and inland populations in British Columbia. In contrast to expectations, the three investigated Swiss populations were genetically neither isolated nor differentiated from each other despite the long‐lasting negative human impact on the lichen's range size in Central Europe. We propose that detailed studies integrating local landscape and regional scales are now needed to understand the processes of dispersal and gene flow in lichens.

Low RAPD Variation and Female-Biased Sex Ratio Indicate Genetic Drift in Small Populations of the Dioecious Conifer Taxus Baccata in Switzerland - Karin Hilfiker; Felix Gugerli; Jean-Philippe Schütz; Peter Rotach; Rolf Holderegger (Conservation Genetics, 2004)

Book review - Rolf Holderegger (Plant Systematics and Evolution, 2003)

Book reviews - Rolf Holderegger (Plant Systematics and Evolution, 2002)

Estimation of the relative importance of sexual and vegetative reproduction in the clonal woodland herb Anemone nemorosa - Rolf Holderegger; Ivana Stehlik; J. Jakob Schneller (Oecologia, 1998)

Localized hybridization betweenSaxifraga aizoides andS. mutata (Saxifragaceae): Reproductive ecology ofS. hausmannii and implications for conservation - Rolf Holderegger (Plant Systematics and Evolution, 1998)